(3LGeY GdeHGOF hGdZGjGJ aj Yde GdejbGJs - (3GdMSf Hf Ydj Hf YeQ, CHh Ydj TQa GdOjf GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3aUd ai GSJYeGd GdehGVY GdeTJQcI ai GdNGUI s
(3BNQgG (B:s
(3Ke NP HGdHQcGQ ef CRGA GdeSWQI eKd GdVdY GdbGFe hVY CMO WQajg ai fbWI L hYde HWQag GdCNQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdadcs